Induction of autophagy improves skin and hair conditions in dogs with underlying diseases - Kim, Yoonji; Lee, Seung-Hwa; Song, Yunji; Jeong, Sekyoo; Kim, Ha-Jung (Frontiers in Veterinary Science, 2023)
Background: Autophagy was reported to play a crucial role in maintaining general and skin health. Methods: The study used a synthesized autophagy inducer (AI) (Aquatide,™ cospharm Inc.; Daejeon, Korea), for evaluating the effects of autophagy on skin and hair in dogs. Twenty-two dogs with poor skin and hair which were diagnosed with canine atopic dermatitis (CAD) or pituitary-dependent hyperadrenocorticism (PDH) were included. Clinical scores using Canine Atopic Dermatitis Extent and Severity Index-04 (CADESI-04), Pruritus Visual Analogue Scale (PVAS) and skin barrier function using measurement of transepidermal water loss (TEWL) were evaluated and canine keratinocytes were also used in vitro investigation of pro-inflammatory cytokines after AI treatment. Results: In the AI group, clinical scores and skin barrier function were improved at week 8 significantly compared to in the other groups. In particular, the AI significantly improved the hair surface damage at 8 weeks compared to the baseline. In vitro, the AI reduced pro-inflammatory cytokines by activating the 78-kDa glucose-regulated protein (GRP78). Conclusion: AI improve skin barrier function and hair damage and reduce pro-inflammatory cytokines by inhibiting reactive oxygen species (ROS) production in dogs.